Analysis of audiological results of patients referred from newborn hearing screening program. - Song, Chan Il; Kang, Ho Seob; Ahn, Joong Ho (Acta Oto-Laryngologica, 2015)
Conclusion:As tools of confirmation of sensorineural hearing loss in neonates who are ‘referred’ from a newborn hearing screening program, both ASSR and DPOAE have high sensitivity and specificity. In addition, ASSR can be used as a substitute for ABR.Objectives:To analyze the confirmative audiological results of patients referred from a newborn hearing screening program.Patients and method:From January 2007 to December 2013, hearing tests were performed on 474 babies (804 ears) who were ‘referred’ from the hospital or other maternity centers. Auditory brainstem response (ABR), auditory steady-state response (ASSR), and distortion product otoacoustic emissions (DPOAE) were used for hearing evaluation.Results:Of 474 babies (804 ears), 232 had normal hearing, while 242 babies (358 ears) had over 30 dB nHL threshold from ABR. Among the 156 babies (312 ears) who underwent both ABR and ASSR, the mean ASSR threshold had a strong correlation with ABR threshold (r= 0.942,p< 0.001). Assuming that ABR results were the yardstick of abnormal hearing, sensitivity and specificity of ASSR to ABR were 90.6% and 95%. DPOAE tests were performed on 180 babies (360 ears), with sensitivity of 85.9% and specificity of 84.4%.